Understanding the household cooking fuel transition. Issue 11 (20th August 2019) - Schunder, Torsten; Bagchi‐Sen, Sharmistha
Abstract: Three billion people use biomass and other harmful cooking fuels (e.g., charcoal) worldwide. This poses a significant risk to health and deters human development. Policies have been implemented to promote the use of modern cooking fuels, but the outcomes have been uneven. The problem continues to affect the poor, especially in rural and remote areas, in disproportionate ways. While technological solutions exist, widespread adoption has been slow due to various barriers to transition at the household level. In this paper, we provide a review of the findings from studies on household cooking fuel transition to show the various factors that affect the process. We not only acknowledge the role of policy but also emphasize the need for understanding the mismatch between broader policy and local household response to policy surrounding cooking fuel use.